Ganoderma lucidum spore oil alleviates psychological stress-evoked tumor progression by enhancing FcγR-mediated macrophage phagocytosis - Dong-Dong Li; Zi-Xuan Li; Yang-Fan Zhou; Ling Jin; Wan-Li Liang; Wen-Dong Xu; Xiang Luo; Guan-Di Xiao; Qi-Jun Chen; Ting Xie; Hui Xu; Yang Liu; et al. (Chinese Medicine)
Abstract Background Ganoderma lucidum (G. lucidum), has been documented as a medicinal herb in classical texts and officially recognized in both Eastern and Western pharmacopeias. G. lucidum spore oil (GLSO), a lipid substance extracted from sporoderm-broken spores, has shown potential in enhancing immune function and prolonging the survival of tumor patients. However, the mechanisms underlying GLSO’s immunomodulatory effects remain poorly unknown. Methods The effect of psychological stress on tumor progression and macrophage phagocytosis was analyzed by an in vivo small animal imaging system and flow cytometry. The effect of psychological stress on phospholipid composition in mice was investigated by LC–MS/MS based lipidomic analysis. The effectiveness of GLSO in tumor-bearing mice subjected to restraint stress was observed by tumor burden and phagocytosis of macrophages. Finally, the underlying mechanism of GLSO on macrophage phagocytosis in mice subjected to psychological stress was explored by RNA-seq, and the FcγR/SYK-mediated macrophage phagocytosis pathway was confirmed by qPCR, Western blotting, and confocal laser technology. Results Our study discovered that psychological stress-triggered tumor progression is contributed to by liposoluble components-impaired macrophage phagocytosis. Lipidomics analysis further identified lysophosphatidylinositol [LPI (18:0)] as a key factor suppressing macrophage phagocytic capacity under psychological stress. GLSO was shown to mitigate psychological stress-evoked tumor progression by enhancing macrophage-mediated phagocytosis of tumor cells in vivo. Mechanistically, transcriptomics analysis revealed that the LPI-mediated FcγR phagocytosis pathway is a crucial axis driving the therapeutic effect of GLSO under psychological stress. Conclusion Our findings illustrate that psychological stress-promoted cancer progression is contributed by the critical liposoluble components LPI (18:0)-mediated FcγR phagocytosis signaling inhibition. GLSO alleviates the dampened phagocytosis of macrophages caused by stress through regulating LPI/FcγR-mediated phagocytosis-related pathways, underscoring its potential as a therapeutic intervention for stress-related tumor progression. Graphical Abstract